Sosialisasi Pencegahan dan Penanganan Infeksi Kulit Pada Santriwati Pondok Pesantren Darul Ulum Batang - Mulia Susanti; Rina Kustriana; Qonita Amalia; Rizki Yuni Novia (Lembaga Pengembangan Kinerja Dosen, 2023)
Dermatitis is a skin disease caused by an inflammatory reaction in the skin due to endogenous, exogenous stimuli and other unknown causes. Endogenous stimuli come from genetic factors, gender, age, race, and history of atopy. Meanwhile, exogenous stimuli come from the type and characteristics of genes, exposure characteristics, and environmental factors. Dermatitis reactions can cause skin infections. Skin infections are a problem that often becomes a major problem in Islamic boarding school environments. The high occupancy rate in Islamic boarding schools, the simultaneous use of facilities, lack of personal and environmental hygiene, as well as the lack of knowledge of the Islamic boarding school students means that cases of skin infections in Islamic boarding schools are still relatively high. For this reason, socialization and education activities are needed for students and female students regarding how to prevent and deal with cases of skin infections with the aim of increasing students' understanding of cases of skin infections and how to prevent them.